Strategic purchasing tactics of health services: a systematic review in cancer - Samereh Yaghoubian; Ghahraman Mahmoudi; Mohammad-Ali Jahani (فصلنامه ابن سینا)
Background: A strategic purchasing is the best way of a win-win situation between a buyer and a service provider. It promotes the financial performance of the health system, protects patients financially, and provides them with appropriate services. This study aimed to investigate the strategic purchasing tactics in cancer patients. Materials and methods: In this systematic review, 13 electronic databases and search engines were searched by appropriate keywords in the time spam of 2000-2018. English or Persian articles on the health issue were discussed, and their quality was evaluated using the CASP checklist. Results: Out of 2,999 identified articles, 21 articles with title, abstract, and text were included in the study. Based on the findings of this study, the main health service purchasing strategies among cancer patients were the strategies of service-recipient, service provider strategy, service-purchaser strategy, and financial tactics with some sub-strategies. Conclusion: Since strategic potentialities in the healthcare organization require a different administrative thinking, the protection and monitoring made by the government in regulating relations among all of stakeholders can improve the quality and cost-effectiveness of service provision and consequent economical profits of the health system.